Books in the Houses of the Burghers of Vilnius in the First Half of the Eighteenth Century - Sarcevičienė, Jolita (Senoji Lietuvos literatūra, 2019)
The circle of problems linked to the burghers’ culture of reading and their relation with books has hardly been addressed in the historiography of Lithuania. In this article, the author resorts to the data of probate inventories compiled in Vilnius from 1700 to 1750 and discusses the sizes of book sets owned by the residents of the city in the first half of the eighteenth century, the linguistic structure of these sets, and their themes. She also gives attention to the functions of books in the urban society of the period discussed.The data obtained from the sources is not sufficient: in hastily written inventories, only a fragment of the book title or only the author’s name is given. Quite often, the books are described by criteria revealing their value: in the inventories, silver-mounted publications would appear among silver objects, and their value would be indicated. Out of 114 probate inventories of the residents of Vilnius compiled during the period discussed, books appear in 48 of them, that is in 42% of inventories. The book sets of the burghers of Vilnius differed notably in their sizes: only nine sets (exceeding twenty books) can at least statistically be called personal libraries. Small book sets, from five to twenty books, appeared six times among those included in the sources. In more than half of the cases–28 of 48 mentions of books in the sources – refer to isolated books, no more than four of them.Based on the data of the sources, a list of 795 books of the burgers of Vilnius was compiled, which became the foundation of the thematic analysis. Unfortunately, it was not possible to identify the language of a rather large number of books (289 items) because the sources give only the number of books present in the home of a particular individual. Of the 506 books the language of which was recorded, 241 (47.6%) were in Latin, 180 (35.6%) in Polish, and 76 (15%) in German. There were some publications in Ruthennian, Czech, and Italian, as well as various dictionaries. Inconsistencies in book registration sources created difficulties in the examination of the themes of the books: of 795 books, the themes of as many as 402 books (more than a half) remained unidentified. Of the 393 books the given titles or authors enabled at least more or less accurate identification of the theme, religious books accounted for about a half (52.6%). Legal literature (14%), historical books (close to 9%), fiction (5.8%) and political sciences (4.5%) lagged well behind. There were even fewer books on other themes (rhetoric, linguistics, philosophy, medicine, and the like). Needless to say, the Bible was the most frequently found book in the homes of the burghers of Vilnius: it appears in 18 of 48 inventories that mention books.Although it is still too early to depict a generalised ‘portrait’ of a book owner, it seems that both wealthy and less affluent residents of Vilnius, men and women owned books; although women had fewer books, they were obviously well cared for, passed on from generation to generation, and possibly used in daily religious practices. Some books were used for studies by young people, while larger libraries were probably accumulated depending on their owner’s professional interests or position occupied. However, such connections are not always noticed, and small sets of books on various themes might point to the owners’ intellectual aspirations, their desire to learn, and their direct personal relationship with a book as a means of spending leisure time. Further research is needed to justify the presumption about the book as a means of spending pastime.Also, the analysed sources provide information on the functions of the book in the society of the period discussed: the book was both a source of knowledge and investment. A silver-mounted book could be a present, a part of a dowry, a collateral asset, and an object of theft. The abundance of religious literature mentioned in the sources suggests a premise of the significance of the book in the spiritual life of the residents of Vilnius. Some book sets point to the relevance of the book in the burghers’ professional activities and to the significance of the book as a tool for learning about the world and reveal diverse cultural horizons of the burghers.
Keywords: book history; Vilnius; personal libraries; book set; probate inventory